(untitled) (Global Journal of Human-Social Science, 2025)
Law N 14 133 2021 assigned senior management the responsibility of implementing a governance model for public procurement However recently introduced governance policies fail to provide clear guidelines to support the selection of procurement portfolios leaving this decision to the manager s discretion This article proposes a governance model tailored to the strategic procurement processes of the Federal Prosecution Service MPF aligned with the objectives of the bidding process as established by the legislation The study adopted applied nature and qualitative approach exploratory and descriptive objectives and was conducted as a single and holistic case study The analysis focused on governance of MPF procurement supported by a literature review on public governance and strategic procurement alongside the examination of institutional documents and archival records As a result an initial normative model was developed and evaluated by experts using the Delphi method The study s key contribution is the draft of a regulation to establish the Strategic Procurement Committee within the MPF introducing the Strategic Procurement Plan a multi-year tool This innovation applicable both to the MPF and the broader public administration fulfills the objectives of Article 11 of Law N 14 133 2021 by defining criteria to ensure the selection of proposals that deliver the most advantageous outcomes for the administration